Von Economo neurons as a specialized neuron class of the human cerebral cortex - Petanjek, Zdravko; Banovac, Ivan; Sedmak, Dora; Prkačin, Matija Vid; Hladnik, Ana (Frontiers in Mammal Science, 2023)
By studying human cortical cytoarchitecture, von Economo (1918) noticed large spindle-shapedneurons within layer Vb in the anterior-cingulate and fronto-insular cortex. Those neurons had such extremely elongated stick-like or corkscrew-like soma shape that appeared to him as a pathological alteration. Eventually, he realized that this was a specialized-type of neuron which he described as distinct from the main cortical cell populations, including the commonly found spindle cells. Data from recent studies suggest that specialized-stick-corkscrew-neurons may have first developed in the frontoinsular cortex before the division of hominids and Old-World monkeys, and that they have become abundant in the anterior-cingulate cortex only in the hominid line. Golgi analysis found that they have distinctive somato-dendritic morphology with a characteristic very distal position of their axon origin. Many additional studies claimed to find cells similar to the specialized cells described by von Economo in other non-primate species, even in functionally unrelated cortical regions and layers. However, these studies did not provide sufficient evidence that the cells they described are indeed distinct from common spindle-shaped-neurons, and that they truly correspond to the specialized-stick-corkscrewcells described by von Economo. We believe that present evidence primarily supports the presence of specialized-stick-corkscrew-neurons in hominids, with a seeming increase in their number in humans compared to other primates. The functional significance of such neuronal specialization within specific areas of the human cerebral cortex remains to be elucidated.